Genetic improvement in draughtability of Hariana breed using behavioural attributes - Yadav, A S; Dhaka, S S; Khanna, A S; Rana, Z S (The Indian Journal of Animal Sciences, 2005)
The study was conducted to improve the draught capacity of Hariana cattle by using behavioural traits and try to locate the attributes responsible for hereditary variation for draught capabilities, efficiency and load fatigue relationship. Male calves (46), half-sib progeny of 11 sires of Hariana breed at 2 teeth stage (= 18 months of age) selected on the basis of their dam’s yield from university herd were utilized. Behavioural attributes measured as fatigue score index increased with increase in duration of work. Our results indicated that behavioural attributes have low to high estimate of heritability (0.08 to 0.61). Year o fwork had significant effect on the performance in terms of draught power in the young bulls of this breed. Leg incoordination attribute had significant positive phenotypic correlations with almost all the traits. The estimates of genetic parameters indicated that the additive genetic variance exists for these attributes and there is ample scope of improvement in draught capacity in this breed.